Proyecto de Inversión para la producción y comercialización de barras de cacao con arándanos en la ciudad de Loja - Sarango Mile, Jairo Giovanni (2024)
The research into the production and commercialization of cocoa bars with blueberries reveals a healthier product for consumers. Also, it capitalizes on the availability of cocoa from the Ecuadorian Amazon, presenting a 55% cocoa bar with blueberries. The goal of this project is to determine its financial feasibility. The study is exploratory-conclusive in nature, with a mixed- method approach that utilizes both deductive and inductive methods, along with documentary review and surveys. In the market study, chocolate bars were identified as direct competitors. Surveys were conducted among residents of Loja city aged between 15 and 65 years, revealing an unmet demand of 544,936 cocoa bars with blueberries of 25 grams each. The technical study shows a production capacity of 141,700 bars, which remains consistent over the project’s 5-year lifespan. The financial study indicates an investment of $16,112.52. The retail price of the 25-gram product is $0.95, with an expected income of $134,898.40 in the first year. The financial evaluation results are as follows: Net Present Value (NPV) of $33,777.93; Internal Rate of Return (IRR) of 85%; Benefit-Cost Ratio (BCR) of $0.17 per dollar invested; Payback Period (PP) of 1 year and 7 months. Sensitivity analysis shows that with a 9.70% increase in costs and an 8.28% decrease in revenues, the sensitivity is 0.99, which is below 1, indicating that project profitability remains unaffected. The project is determined to be viable for execution.